enter image description here

In Ceva's Theorem, I understand that $\dfrac{A_{\triangle PXB}}{A_{\triangle PXC}}=\dfrac{BX}{CX}=\dfrac{A_{\triangle BXA}}{A_{\triangle CXA}}$.

I would like clarification in understanding the following step which states:

$$\frac{A_{\triangle APB}}{A_{\triangle APC}}=\frac{A_{\triangle AXB} - A_{\triangle PXB}}{A_{\triangle AXC}-A_{\triangle PXC}}=\frac{BX}{CX}$$

How does the subtraction of the two areas make it so that the new triangles, even though they do not share those sides, are still proportional to $\frac{BX}{CX}$?


$A_{\triangle AXB}: A_{\triangle AXC}=BX:CX\Rightarrow A_{\triangle AXB}=\frac{BX}{CX}A_{\triangle AXC}$

$A_{\triangle PXB}: A_{\triangle PXC}=BX:CX\Rightarrow A_{\triangle PXB}=\frac{BX}{CX}A_{\triangle PXC}$

Hence $$\frac{A_{\triangle A X B} -A _{\triangle P X B}}{A _{\triangle A X C}-A_{ \triangle P X C}}=\frac{\frac{BX}{CX}A_{\triangle AXC}-\frac{BX}{CX}A_{\triangle PXC}}{A _{\triangle A X C}-A_{ \triangle P X C}}=\frac{BX}{CX}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.